Nanoscale metallic‐organic frameworks as an advanced tool for medical applications: Challenges and recent progress. (2nd January 2023) - Pourmadadi, Mehrab; Ostovar, Shima; Eshaghi, Mohammad Mahdi; Rajabzadeh‐Khosroshahi, Maryam; Safakhah, Sara; Ghotekar, Suresh; Rahdar, Abbas; Díez‐Pascual, Ana M.
Abstract : Recently, metal‐organic frameworks (MOFs) have received a lot of interest for application in many fields ranging from catalysis, energy storage, and gas sensing to chemosensory and biomedicine owed to their flexible composition, tunable porosity, and easy functionalization ability. In particular, nanoscale MOFs have been broadly investigated as carriers for the delivery of therapeutics to cancerous organs owed to their high encapsulating capacity and controlled cargo release, versatility, biodegradability, and good biocompatibility. Several methods such as solvothermal, mechanochemical, electrochemical, microwave, and ultrasound have been utilized to fabricate MOFs via custom‐made synthesis. Many efforts have been made to functionalize MOFs through "post‐synthetic modification, " by adjusting the nature, size, and charge of the linkers or tuning its main components. Herein, a comprehensive literature review on recent papers dealing with drug‐loaded MOFs for the detection and treatment of cancer as well as bacterial, fungal, and viral infections is presented. Different types of MOFs applied as carriers in drug delivery systems and biosensing platforms are described. Furthermore, perspectives and challenges for future research in the field, particularly for cancer therapy, are discussed. Thus, very limited literature is available on in vitro and in vivo toxicity of nanoscale MOFs. Besides, their biological stability and long‐term safety are crucial factors that should be further investigated. Based on the reviewed papers, zeolite imidazolate framework (ZIF) and Materials of Institute Lavoisier (MIL) families have been the main focus for drug delivery and diagnosis applications, respectively, while many types of MOFs have exhibited antibacterial and antifungal properties regardless of their cargo. Abstract : Metal‐organic frameworks (MOFs) have been broadly investigated as carriers for drug delivery owed to their high encapsulating capacity and controlled cargo release, versatility, biodegradability, and good biocompatibility. Herein, a comprehensive literature review on drug‐loaded MOFs for the diagnosis and therapy of cancer, for the treatment of bacterial, fungal, and viral infections as well as in the field of immunotherapy is presented.